Salidroside protects against high-altitude hypoxia-induced kidney injury via regulation of renal dopamine D1-like receptors - Cheng Huan; Gan Zhilin; Xiao Dan; Wang Yue; Li Xianglian; Mo Liwen; Cheng Yue (PLoS ONE, 2026)
High-altitude hypoxia is a well-established risk factor for acute kidney injury (AKI), yet effective therapeutic options remain scarce. Salidroside, the primary active compound extracted from Rhodiola, has been reported to protect against hypoxia-induced damage in various organs. Here, we aimed to determine whether salidroside could alleviate kidney injury caused by acute high-altitude exposure and to investigate its underlying mechanisms. To this end, male Sprague-Dawley rats were exposed to hypobaric hypoxia simulating an altitude of 5000 meters and were treated with different doses of salidroside. Kidney injury biomarkers, including neutrophil gelatinase-associated lipocalin (NGAL), kidney injury molecule-1 (KIM-1), and cystatin C (Cys-C), were measured in serum and urine. Histological analysis and protein expression levels of dopamine D1-like receptor (DRD1) and G protein-coupled receptor kinase 4 (GRK4) were also evaluated. In parallel, primary renal proximal tubular (RPT) cells from rats were cultured under hypoxic conditions to validate the findings in vitro, with additional groups receiving DRD1-targeting siRNA or the DRD1 agonist fenoldopam. Salidroside significantly reduced biomarker levels of kidney injury in vivo, preserved DRD1 expression, and inhibited GRK4 upregulation in a time- and dose-dependent manner. Likewise, in vitro treatment with salidroside enhanced cell viability and decreased apoptosis while restoring DRD1 levels and downregulating GRK4. Notably, the protective effects were abolished by DRD1 knockdown and enhanced by fenoldopam, indicating a DRD1-dependent mechanism. Molecular docking analysis further supported these results by demonstrating strong binding affinities between salidroside and both DRD1 and GRK4. Together, our findings suggest that salidroside attenuates hypoxia-induced renal injury through modulation of intrarenal dopamine signaling and highlight its potential as a preventive or therapeutic agent for individuals exposed to hypobaric hypoxia.